Nutrition management for children with diarrhea - Dian Novita Chandra (Indonesian Nutrition Association, 2020)
Diarrhea in children, especially if it recurs or persistent, can have an impact on the nutritional status of the child and lead to stunting. Apart from that, diarrhea also has an impact on children's cognitive in the future, regardless of their nutritional status.